Herbivore‐specific induction of defence metabolites in a grass–endophyte association. (29th September 2016) - Fuchs, Benjamin; Krischke, Markus; Mueller, Martin J.; Krauss, Jochen
Summary: Plants have developed a variety of defence strategies against herbivores. One possible strategy is the induced production of metabolites following herbivore attack. Plant‐associated micro‐organisms can be the source of such defensive compounds. For example, cool‐season grasses can be associated with systemic endophytic fungi of the genus Epichloё, which produce herbivore‐toxic alkaloids. In a controlled common garden approach, we tested the hypothesis that different types of herbivory induce endophyte growth and increase the endophyte‐mediated production of three bioactive alkaloids which can deter or toxify herbivores. During 18 weeks, we analysed biweekly endophyte and alkaloid concentrations in the grass Lolium perenne infected with the endophytic fungus Epichloё festucae var. lolii . The experiment was conducted throughout the field season and compared three different herbivore treatments to the control treatment (herbivory exclosure). We showed that the concentration of the vertebrate toxic alkaloid lolitrem B increased following clipping (a simulation of grazing herbivores), while the insect deterring alkaloid peramine increased following locust herbivory (biting–chewing herbivores). The endophyte concentration increased slightly following clipping ( P  = 0·09). Sap sucking aphids altered neither endophyte nor alkaloid concentrations. Our study provides evidence for an herbivore‐specific induction of endophyte‐mediated responses following herbivore attack on its host grass. Our results suggest that the grass–endophyte symbiosis involves a close chemical crosstalk between the interacting partners. Abstract : Lay Summary